Brief Report: Flow Rate of Cerebrospinal Fluid Through a Spinal Needle Can Accurately Predict Intracranial Pressure in Cryptococcal Meningitis. (1st March 2017) - Boyles, Tom H.; Gatley, Elizabeth; Wasserman, Sean; Meintjes, Graeme
Abstract : Background: Patients with HIV-associated cryptococcal meningitis (CM) commonly present with raised intracranial pressure (ICP). Aggressive management of raised ICP reduces mortality but requires manometers, which are unavailable in most resource-limited settings. The law of Poiseuille states that the rate of flow of liquid through a tube is directly proportional to the difference in pressure between each end, and it may be possible to indirectly determine ICP by measuring flow of CSF through a spinal needle rather than using a manometer. Methods: A convenience sample of CM patients requiring lumbar puncture (LP) (with 22-G spinal needle) for ICP measurement and control were enrolled. ICP was first measured using a narrow bore manometer. After removing the manometer, the number of drops of CSF flowing from the spinal needle in 15 seconds was counted. Results: Thirty-two patients had 89 LPs performed (range, 1–23). Fifty-four had high opening pressure with a CSF flow rate of 16–200 drops/min, and 35 had normal pressure with a CSF flow rate of 8–140 drops/min. Area under the fitted receiver operator character curve was 0.89. A flow rate cutoff to define high pressure of ≥40 drops/min correctly classified 75 of 89 LPs (accuracy 84%). Conclusions: It is technically feasible to indirectly estimate CSF pressure to an accuracy that is clinically useful by counting drops of CSF flowing from a spinal needle. The optimal cutoff value for defining high pressure using a standard 22-G spinal needle is ≥40 drops/min. These findings have the potential to improve CM management in resource-limited settings.